2012
DOI: 10.1186/1472-6793-12-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 beta: a potential link between stress and the development of visceral obesity

Abstract: BackgroundA disproportionate amount of body fat within the abdominal cavity, otherwise known as visceral obesity, best predicts the negative health outcomes associated with high levels body fat. Growing evidence suggests that repeated activation of the stress response can favor visceral fat deposition and that visceral obesity may induce low-grade, systemic inflammation which is etiologically linked to the pathogenesis of obesity related diseases such as cardiovascular disease and type 2 diabetes. While the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 161 publications
1
36
0
2
Order By: Relevance
“…All these mechanisms are operative in human adipose tissue and appear to be more pronounced in human visceral compared to subcutaneous tissue [19]. Repeated stress-induced IL-1b production in white adipose tissue may result in functional impairments that drive the development of stress-induced visceral obesity [93].…”
Section: Approaches Targeting Il-1mentioning
confidence: 99%
“…All these mechanisms are operative in human adipose tissue and appear to be more pronounced in human visceral compared to subcutaneous tissue [19]. Repeated stress-induced IL-1b production in white adipose tissue may result in functional impairments that drive the development of stress-induced visceral obesity [93].…”
Section: Approaches Targeting Il-1mentioning
confidence: 99%
“…Obesity is associated with a state of chronic low-grade inflammation and increased circulating inflammatory cytokines, which are linked to the pathogenesis of obesity-related diseases, such as cardiovascular disease and type-2 diabetes [1518]. Coincidental with this chronic inflammation, NLRP3 inflammasome activity is increased in obese individuals, as a result of adipocyte hypertrophy, hypoxia due to poor vascularization of expanding adipose tissue and necrotic cell death, leading to reactive oxygen species (ROS) production and the release of free fatty acids (FFAs) and inflammatory cytokines [1921].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The repeated exposure to psychosocial stress has been linked to the development of visceral obesity. 9 Methylation studies have also demonstrated that distressing life events can alter the expression of variants through effects on promoter DNA methylation. 10 These findings support the need to understand the relationship between genetic susceptibility, psychosocial stress, and metabolic factors acting in combination to increase the risk of CVD.…”
Section: Introductionmentioning
confidence: 99%